AN OVERVIEW OF GROWTH AND DEVELOPMENT OF TODDLERS IN SINGLE-PARENT FAMILIES - Handayani, Maulina; Gymnastiar, Zoga; Lestari, Kustati Budi; Damiati, Nia; Palupi, Puspita (Journal of Maternity Care and Reproductive Health, 2026)
Single parents are individuals who raise and care for their children independently without a partner in daily caregiving roles. This condition may affect toddler growth and development due to limited family support, parenting practices, and stimulation. However, research specifically examining the impact of single-parent status on toddler growth and development remains limited. This study aimed to describe the growth and development of toddlers raised by s. A descriptive quantitative study with a cross-sectional design was conducted using snowball sampling, involving 38 respondents. Data were collected using a weighing scale, stature meter, infantometer, and the Pre-Screening Developmental Questionnaire (KPSP). Most s were mothers (81.6%), predominantly aged 36–45 years. The mean age of toddlers was 46.42 months, with a higher proportion of girls (57.9%). Based on weight-for-height, 60.5% of toddlers had normal nutritional status, while 23.7% were overweight and 10.5% obese. Height-for-age assessment showed 52.6% normal, 28.9% tall, and 18.4% stunted. Developmental assessment indicated questionable development in 47.4% of toddlers and developmental deviation in 7.9%. Single parents are encouraged to receive education on nutritional monitoring and adequate stimulation. Future studies should involve larger samples and use correlational methods to further examine this relationship.